The Spatial Pattern of Cochlear Amplification - Fisher, Jonathan A. N.; Nin, Fumiaki; Reichenbach, Tobias; Uthaiah, Revathy C.; Hudspeth, A. J. (Neuron, 2012)
Sensorineural hearing loss, which stems primarily from the failure of mechanosensory hair cells, changes the traveling waves that transmit acoustic signals along the cochlea. However, the connection between cochlear mechanics and the amplificatory function of hair cells remains unclear. Using an optical technique that permits the targeted inactivation of prestin, a protein of outer hair cells that generates forces on the basilar membrane, we demonstrate that these forces interact locally with cochlear traveling waves to achieve enormous mechanical amplification. By perturbing amplification in narrow segments of the basilar membrane, we further show that a cochlear traveling wave accumulates gain as it approaches its peak. Analysis of these results indicates that cochlear amplification produces negative damping that counters the viscous drag impeding traveling waves; targeted photoinactivation locally interrupts this compensation. These results reveal the locus of amplification in cochlear traveling waves and connect the characteristics of normal hearing to molecular forces.
CRIS-Team Scopus Importer:2021-02-25